Guest Editorial: The 23rd International Conference on Control, Automation, and Systems (ICCAS 2023) - Eun, Yongsoon (International journal of control, automation, and systems, 2024)
This special issue is dedicated to the papers that extended the work presented at the 23rd International Conference on Control, Automation, and Systems (ICCAS 2023), held Yeosu Venezia Hotel & Utop Marina Hotel, Korea, from October 17∼20, 2023. Because ICCAS aims to bring together researchers and engineers in the fields of control, automation, robotics, and systems engineering, the scope of the conference is well aligned with the scope of the International Journal of Control, Automation, and Systems (IJCAS). Thus, this special issue is pursued as part of the effort to solicit publications of the latest results in the relevant fields to IJCAS. The submitted papers underwent a rigorous review process for the quality and significance of the work. In addition, all selected papers are based on the ICCAS 2023 presentation and include substantial extension from the original presentation. Out of 18 submissions, a total of 13 papers were for publication: 1. Model Predictive Current Control for Grid-connected Inverter Considering the PLL Dynamics by Sivadharshini A, Ngoc-Duc Nguyen, and Young Il Lee2. Overcoming Delayed Feedback in Reinforcement Learning Using Actor Ensembles by Jongsoo Lee, Jonghyeok Park, and Soohee Han3. Quadrotor Dynamics in a Wind Field: Equilibria Analysis and Energy Dissipation by Minhyeok Kwon and Yongsoon Eun4. Robust PCA-based Walking Direction Estimation via Stable Principal Component Pursuit for Pedestrian Dead Reckoning by Jae Wook Park, Jae Hong Lee, and Chan Gook Park5. IS-YOLO: A YOLOv7-based Detection Method for Small Ship Detection in Infrared Images With Heterogeneous Backgrounds by Indah Monisa Firdiantika and Sungho Kim6. Image Quality Assessment in Visual Reinforcement Learning for Fast-moving Targets by Sanghyun Ryoo, Jiseok Jeong, and Soohee Han7. Data-driven Fault Diagnosis of Nonlinear Systems With Parameter Uncertainty Using Deep Koopman Operator and Weighted Window Extended Dynamic Mode Decomposition by Jayden Dongwoo Lee, Lamsu Kim, Seongheon Lee, andHyochoong Bang8. A Cable-driven Parallel Robot for High-rack Logistics Automation by Seong-Hun Ha, Seong-Woo Woo, Min-Cheol Kim, Jinlong Piao, Gyoung-Hahn Kim, Md Sahin Sarker, Bae-Jeong Park, Sejeong Kim, Myungjin Jung, Keum-ShikHong, and Chang-Sei Kim9. Development of a Hybrid Gripper With Jamming Module Using Small-scale Pneumatic Pump by Myeongjin Kim, Jingon Yoon, Donghyun Kim, and Dongwon Yun10. Path-tracking Robust Model Predictive Control of an Autonomous Steering System Using LMI Optimization With Independent Constraints Enforcement by Nguyen Ngoc Nam and Kyoungseok Han11. Sparse Instantiation of Bias Nodes for Factor Graph-based Terrain-referenced Navigation by Junwoo Park and Hyochoong Bang12. Buffer Parameter Optimization for Advanced Automated Material Handling Systems in Serial Production Lines by Seunghyeon Kim, Kyung-Joon Park, and Yongsoon Eun13. Fault Detection for Re-initialization of Online Gaussian Process Regression Using Kernel Linear Independence Test by Lamsu Kim, Jayden Dongwoo Lee, Seongheon Lee, and Hyochoong Bang Moving forward, the editorial board of IJCAS plans to continue its efforts in identifying exceptional papers from future editions of the International Conference on Control, Automation, and Systems (ICCAS) for potential publication at IJCAS. KCI Citation Count: 0